The Edible Mushroom Pleurotus spp.: I. Biodiversity and Nutritional Values - Maftoun, Parisa; Johari, Helmi; Soltani, Mohammad; Malik, Roslinda; Othman, Nor Zalina; El Enshasy, Hesham A. (International Journal of Biotechnology for Wellness Industries, 2015)
Mushrooms are macrofungi with numerous varieties and widely known as food and medicine in many ancient cultures. They are considered as potential source of many essential nutrients as well as therapeutic bioactive compounds and thus became one of the main components in Traditional Chinese Medicine (TCM) and in Japanese herbal medicine since more than two thousand years. The genus Pleurotus (widely known as oyster mushroom) is fast growing fungus belongs to basidiomycota group and considered as one of the famous species with many health benefits. Nowadays, seventy species of this genus has been discovered, but solely a few of them such as P. florida, P. sajor-caju and P. ostreatus are available in the market. The rich nutrients such as proteins, fibers, carbohydrates, minerals, vitamins, and lipids present this mushroom as famous healthy food. Furthermore, Bioactive compounds such as polysaccharides, proteins and nucleic acid are extracted from various species of Pleurotus tends the researcher to investigate more on this beneficial genus. This work is focused on reviewing the recent work published in the biodiversity and nutritional content of Pleurotus spp.